Hepatoprotective effects of Aureobasidium pullulans derived Beta 1,3-1,6 biological response modifier glucans in a STAM- animal model of non-alcoholic steatohepatitis - Ikewaki, Nobunao; Kurosawa, Gene; Iwasaki, Masaru; Preethy, Senthilkumar; Dedeepiya, Vidyasagar Devaprasad; Vaddi, Suryaprakash; Senthilkumar, Rajappa; Levy, Gary A; Abraham, Samuel JK (bioRxiv, 2021)
Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) are highly prevalent conditions characterized by inflammation and fibrosis of the liver which can progress to cirrhosis and hepatocellular carcinoma if left untreated. Lifestyle disorders such as obesity, diabetes and dyslipidaemia predispose to and are associated with the disease progression. Conventional modalities are mainly symptomatic, with no definite solution. Beta glucan-based biological response modifiers are a potential strategy in lieu of their beneficial metabolic effects. Aureobasidium pullulans strains AFO-202 and N-163 beta glucans were evaluated for anti-fibrotic and anti-inflammatory hepatoprotective potentials in a NASH animal model in this study. In the STAM™ murine model of NASH, five groups were studied for eight weeks— (1) vehicle (RO water), (2) AFO-202 beta glucan; (3) N-163 beta glucan, (4) AFO-202+N-163 beta glucan, and (5) telmisartan (standard pharmacological intervention). Evaluation of biochemical parameters in plasma and hepatic histology including Sirius red staining and F4/80 immunostaining were performed. AFO-202 beta glucan significantly decreased inflammation-associated hepatic cell ballooning and steatosis. N-163 beta glucan decreased fibrosis and inflammation significantly (p value<0.05). The combination of AFO-202 with N-163 significantly decreased the NAFLD Activity Score (NAS) compared with other groups. This preclinical study supports the potential of N-163 and AFO-202 beta glucans alone or in combination as potential preventive and therapeutic agent(s), for NASH.